Restoration of Post Root Canal Treatment - Kalalo, Williyam W.; Khoman, Johanna A,; Supit, Aurelia S. R. (Universitas Sam Ratulangi, 2022)
Abstract: Root canal treatment is a part of dental conservation treatment which aims to treat damaged tooth and pulp necrosis in order to maintain the tooth’s function, and to restore the condition of the diseased tooth. The type of dental restoration after root canal treatment must be considered based on indications as well as the support of the surrounding teeth and tissues. An ideal dental restoration must protect the missing occlusal and cusp surfaces, therefore, it can protect the tooth crown structure as much as possible. This study aimed to evaluate types and indications of post-root canal restoration. This was a literature review study using three databases namely Google Scholar, Garuda, and Pubmed. The results obtained nine articles of case reports. There were various types of restoration used in post-root canal treatment as follows: direct resin composite with onlay preparation; porcelain fused to metal; fiber post restoration and porcelain fused to metal; porcelain fused to metal and customed dowel; endocrown; fiber reinforced composite; porcelain onlay restoration; fiber reinforced composite; and fiber and porcelain fused to metal. A good restoration was able to restore the tooth’s function. In conclusion, there are various types of restoration options in this study. All are good to be used in post-root canal treatment, regarding their indications and usages. Moreover, porcelain restoration is an affordable and robust restoration.Keywords: restoration; root canal treatment Abstrak: Perawatan saluran akar merupakan salah satu perawatan konservasi gigi yang bertujuan untuk merawat gigi yang mengalami kerusakan dan nekrosis pulpa agar gigi tersebut tetap dapat berfungsi. Pemilihan jenis restorasi gigi pasca perawatan saluran akar harus memperhatikan indikasi penggunaan atau melihat dukungan dari gigi atau jaringan sekitar gigi. Restorasi gigi yang ideal harus melindungi permukaan oklusal dan cusp yang hilang sehingga secara maksimal dapat melindungi struktur mahkota gigi. Penelitian ini bertujuan untuk menelusuri restorasi pasca perawatan saluran akar. Jenis penelitian berupa literarure review menggunakan database google scholar, Garuda, dan pubmed. Hasil penelitian mendapatkan sembilan artikel laporan kasus. Terdapat banyak pilihan jenis restorasi pasca perawatan saluran akar yaitu: direk resin komposit preparasi onlay; porcelain fused to metal; pasak dan porcelain fused to metal; porcelain fused to metal and customed dowel; endocrown; fiber reinforced composite; restorasi onlay porcelain; fiber reinforced composite; dan pasak fiber and porcelain fused to metal. Restorasi yang baik harus memperhatikan pengembalian fungsi gigi. Simpulan penelitian ini ialah terdapat berbagai pilihan jenis restorasi yang dapat digunakan pasca perawatan saluran akar. Semua pilihan jenis restorasi ini baik untuk digunakan pasca perawatan saluran akar, namun harus mempertimbangkan indikasi dan penggunaan restorasi. Restorasi dengan bahan porselen merupakan restorasi yang terjangkau dan kuat.Kata kunci: restorasi; perawatan saluran akar